Development based on geopark concept case study Pulau Langkawi, Kedah / Nurul Izza Muhamad - Muhamad, Nurul Izza (2012)
The concept of development is the basis of planning law, all development must refer to the requirements and provisions of the Town and Country Planning Act 1976. According to Town and Country Planning Act 1976 (Act 172) development can be defined any work an building, mining engineering , industrial and any similar work in, on beside or below ground or made any material change of use of any buildings. This definition has two meaning first operations / work and second material change in use. Word of ‘development’ can be defined as the process of developing or being developed (ref) For example the process of converting land for a new purpose by consulting building or making use of its resources. Development can be classified as a change that can be seen from the poor condition to a better condition or also can say from an undeveloped to developed (Nazimah, 2008). According to Mazha (2010), development is the changes in political, economic, and social and also the infrastructure that occurred in an area due to development in the construction sector, manufacturing sector, education sector also in the communication sector and its accordance with the increase in population.